KISAH KAUM NABI LÛTH DALAM AL-QUR’AN DAN RELEVANSINYA TERHADAP PERILAKU PENYIMPANGAN SEKSUAL - Santi Marito (Institut agama islam negeri Padangsidimpuan, 2019)
This research is motivated by the increasingly widespread existence of homosexuals; this is evidenced by their increasing number every year. In 2015 the Indonesian Ministry of Health noted that there were 25,412 cases of homosexuals infected with HIV, in 2016 reaching 28,640 cases. In addition, homosexuals and their supporters try to legalize fellow marriages. They use the jargon